Annual influenza vaccination reduces total hospitalization in patients with chronic hepatitis B virus infection: A population-based analysis. Issue 1 (2nd January 2016) - Su, Fu-Hsiung; Huang, Ya-Li; Sung, Fung-Chang; Su, Chien-Tien; Hsu, Wen-Hsin; Chang, Shih-Ni; Yeh, Chih-Ching
Abstract: Background: This study evaluated hospitalization and mortality in patients with chronic hepatitis B virus infection (HBV (+)) and matched comparison patients after stratifying the patients according to annual influenza vaccination (Vaccine (+)). Methods: Data from Taiwan's National Health Insurance program from 2000 to 2009 were used to identify HBV(+)/vaccine(+) ( n  = 4434), HBV(+)/Vaccine(−) ( n  = 3646), HBV(−)/Vaccine(+) ( n  = 8868), and HBV(−)/Vaccine(−) ( n  = 8868) cohorts. The risk of pneumonia/influenza, respiratory failure, intensive care, hospitalization, and mortality in the four cohorts was evaluated. Results: The total hospitalization rate was significantly lower in patients with chronic HBV infection who received an annual influenza vaccination than in chronic HBV-infected patients who did not receive an influenza vaccination (16.29 vs. 24.02 per 100 person-years), contributing to an adjusted hazard ratio (HR) of 0.56 (95% confidence interval (CI) = 0.50–0.62). The HBV(+)/Vaccine(+) cohort also had lower risks than the HBV(+)/Vaccine(−) cohort for pneumonia and influenza (adjusted HR = 0.79, 95% CI = 0.67–0.92), intensive care unit admission (adjusted HR = 0.33, 95% CI = 0.25–0.43), and mortality (adjusted HR = 0.19, 95% CI = 0.15–0.24). Conclusions: Our results suggest that annual influenza vaccination can reduce the risk of hospitalization and mortality in patients with chronic HBV infection.